Zero-spacing interferometer for measurement of continuum spectrum of the low radio frequency background - Raghunathan, A.; Patra, N.; Shankar, N.; Ekers, Ronald; Subrahmanyan, R. (2011)
We have developed an interferometer method for measurement of broad-band spectrum of the low radio frequency celestial radiation background, which is of importance in understanding the Epoch of Reionization, when the first stars and galaxies formed in the evolving universe. We have used two antennas in a short-spacing east-west interferometer mode, with a resistive semi-transparent screen in between. The system operates in the frequency range 87.5 to 175 MHz, suitable for probing the evolution in the state of the gas during cosmological epochs in the redshift range 7 - 15. © 2011 IEEE.